2018
DOI: 10.1021/acsphotonics.8b00288
|View full text |Cite
|
Sign up to set email alerts
|

Rare-Earth Monopnictide Alloys for Tunable, Epitaxial, Designer Plasmonics

Abstract: We demonstrate that plasmonic response can be tuned spectrally via the alloy composition of an epitaxial semimetallic film. Specifically, attenuated total reflectance studies show that the surface plasmon resonance of rare-earth monopnictide La x Lu1–x As alloy films can be tuned across the mid-IR, while lattice-matching to technologically important substrates. The electrical properties are a strong function of the composition, which, in turn, manifests as tunability of the optical properties. The ability to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…This provides an opportunity to grow epitaxial self‐assembled anisotropic plasmonic and metamaterial device structures. Although Ln‐V materials have been demonstrated as components in high‐performance thermoelectrics, tunnel junctions, and photoconductive switches, many Ln‐V materials are also interesting for plasmonic devices due to their (semi)metallic properties . ErAs nanoparticles (NPs) embedded in GaAs show sharp attenuation peaks below the GaAs band edge which was controversially attributed to a particle surface‐plasmon resonance .…”
Section: Sample Parameters Of Nine Co‐deposited Eras:gaas Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides an opportunity to grow epitaxial self‐assembled anisotropic plasmonic and metamaterial device structures. Although Ln‐V materials have been demonstrated as components in high‐performance thermoelectrics, tunnel junctions, and photoconductive switches, many Ln‐V materials are also interesting for plasmonic devices due to their (semi)metallic properties . ErAs nanoparticles (NPs) embedded in GaAs show sharp attenuation peaks below the GaAs band edge which was controversially attributed to a particle surface‐plasmon resonance .…”
Section: Sample Parameters Of Nine Co‐deposited Eras:gaas Filmsmentioning
confidence: 99%
“…ErAs nanoparticles (NPs) embedded in GaAs show sharp attenuation peaks below the GaAs band edge which was controversially attributed to a particle surface‐plasmon resonance . A recent study demonstrated that La x Lu 1− x As ternary alloy ( x = 0–1) films are tunable designer plasmonic materials across the 3–8 µm range, and the lattice constant of the ternary alloy can be tuned to match to some common III–V substrates . However, despite the potential of (semi)metallic Ln‐Vs as tunable plasmonic materials across the short‐wave to mid‐IR range, as well as the ability of being epitaxially combined with III–V‐based devices, the plasmonic properties of Ln‐V:III–V nanocomposites are still poorly understood.…”
Section: Sample Parameters Of Nine Co‐deposited Eras:gaas Filmsmentioning
confidence: 99%
“…Rare-earth monopnictides are of immense technological and scientific interest due to their potential applications in terahertz sources [1][2][3], thermoelectrics [4], solar cells [5], plasmonics [6], and as buried epitaxial contacts [7] when incorporated in III-V semiconductor heterostructures. Recently, it has been realized that these compounds also exhibit remarkably large magnetoresistance that has been attributed to either electronhole compensation [8][9][10] or the presence of topologically nontrivial surface states [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Shouvik Chatterjee, 1, * Shoaib Khalid, 2, 3 Hadass S. Inbar,4 Aranya Goswami,1 Felipe Crasto de Lima,3 Abhishek Sharan, 2, 3 Fernando P. Sabino,3 Tobias L. Brown-Heft,4 Yu-Hao Chang,4 Alexei V. Fedorov,5 Dan Read,6 Anderson Janotti, 3 and Christopher J. Palmstrøm 1, 4, *…”
mentioning
confidence: 99%
“…RE-V thin films have been epitaxially grown on III-V semiconductors [1][2][3] and sought as structurally perfect (defect-free) epitaxial contacts, 1,4 as nanoparticles embeded in III-Vs for thermoelectrics, infrared and terahertz generation and detection. [5][6][7][8][9][10] Some members of this material family display interesting properties such as extremely large magneto-resistance and non-trivial topological phase including a recently observed unusual magnetic splitting phenomenon. [11][12][13][14][15][16][17] The relatively small overlap in energy between the electron and hole pockets have led researchers to expect that this overlap could be lifted and a band gap would ultimately be opened in structures with reduced dimension such as nanoparticles or thin films due to the quantum confinement effect (QCE).…”
mentioning
confidence: 99%